2011
DOI: 10.5093/cl2011v22n1a2
|View full text |Cite
|
Sign up to set email alerts
|

Resiliencia, Personalidad Resistente y Crecimiento en Cuidadores de Personas con Demencia en el Entorno Familiar: Una Revisión

Abstract: Resumen. La investigación en torno al cuidado no profesional de mayores con demencia ha proliferado a lo largo de los últimos años, constatando muchos autores que, del mismo modo en que el cuidado se asocia a un buen número de consecuencias negativas, diversos efectos positivos pueden derivarse de esta experiencia. Sin embargo, y a pesar del impacto de la corriente positiva en la actualidad, son muy escasos los estudios que valoran la personalidad resistente (hardiness), la resiliencia y el crecimiento persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 48 publications
1
5
0
3
Order By: Relevance
“…With regard to psychological well-being and the general characteristics of the care situation, we only observed significant data among the time dedicated as a caregiver and the positive relations and personal growth scales, in a way that the participants providing continuous care for a longer time had more positive relations and a higher perception regarding their own evolution and positive learning. This result is consistent with that reported by Fernández-Lansac and Crespo (2011), who found that many caregivers described personal growth experiences derived from this role.…”
Section: Matínsupporting
confidence: 93%
“…With regard to psychological well-being and the general characteristics of the care situation, we only observed significant data among the time dedicated as a caregiver and the positive relations and personal growth scales, in a way that the participants providing continuous care for a longer time had more positive relations and a higher perception regarding their own evolution and positive learning. This result is consistent with that reported by Fernández-Lansac and Crespo (2011), who found that many caregivers described personal growth experiences derived from this role.…”
Section: Matínsupporting
confidence: 93%
“…Por tanto, el concepto de resiliencia tiene que ver con la habilidad de recuperarse de eventos negativos (Becoña, 2006). Para que se suscite esta capacidad, es necesaria la exposición de una persona a situaciones adversas y de riesgo (Fernández-Lansas & Crespo, 2011;Luthar et al, 2000;Masten, Cutuli, Herbers & Reed, 2009). El proceso de resiliencia debe incluir determinantes y efectos (Windle, Bennet & Noyes, 2011).…”
Section: Resilienciaunclassified
“…It would therefore be of interest in future research to undertake the study of variables which can orient specific strategies and personal resources that need to be promoted in these women; in other words, those variables that could influence how they cope with their caregiving tasks, and what would help determine risk factors and protection from developing burnout, in general and in each of its dimensions, and from affecting their physical and emotional health in their personal situation. In view of all of the above, previous studies on burnout, and in particular, those focusing on caregiving, have found that some of these variables could be, for example, the quality of the relationship between the caregiver and the patient before the need for care arose, self-care of the caregiver herself, their feelings of competence, resilience, post-traumatic growth, and the type of coping strategy employed (see Avargues-Navarro et al, 2010;Fernández-Lansac and Crespo, 2011;Hodgins et al, 2011;Díaz and Ponsada, 2017;Navarro-Abal et al, 2017;Pérez-San-Gregorio et al, 2017;Campos-Puente et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This shows that emotional affectation is temporary and associated with the specific conditions of the context and the caregiver role at that time (Cequera and Galvis, 2014). Although it cannot be affirmed that caregiving is the direct cause of the high scores on depressive symptomatology, its influence would probably be considerable because of its implications for potentially high stress (Fernández-Lansac and Crespo, 2011;Armon et al, 2014). In fact, depression levels in informal caregivers are associated with lack of resources and social support and perceived overburden due to the work of caregiving (Tuithof et al, 2015).…”
Section: Introductionmentioning
confidence: 99%